Finite geometric structures and their applications lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 19-27, 1972 - Barlotti, A. (Adriano) 1923- (CIME summer schools, 2011)
R.C. Bose: Graphs and designs.- R.H. Bruck: Construction problems in finite projective spaces.- R.H.F. Denniston: Packings of PG(3,q).- J. Doyen: Recent results on Steiner triple systems.- H. Lüneburg: Gruppen und endliche projektive Ebenen.- J.A. Thas: 4-gonal configurations.- H.P. Young: Affine triple systems